2017
DOI: 10.1038/s41467-017-01381-y
|View full text |Cite
|
Sign up to set email alerts
|

CCDC88B is required for pathogenesis of inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) involves interaction between host genetic factors and environmental triggers. CCDC88B maps within one IBD risk locus on human chromosome 11q13. Here we show that CCDC88B protein increases in the colon during intestinal injury, concomitant with an influx of CCDC88B+lymphoid and myeloid cells. Loss of Ccdc88b protects against DSS-induced colitis, with fewer pathological lesions and reduced intestinal inflammation in Ccdc88b-deficient mice. In a T cell transfer model of colitis, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 41 publications
5
44
0
Order By: Relevance
“…7 In humans, the CCDC88B gene maps within a locus on Chromosome 11 (11q13) that contains >20 genes in linkage disequilibrium that is associated with susceptibility to several inflammatory conditions including psoriasis, primary biliary cirrhosis, MS, and inflammatory bowel disease (IBD). [11][12][13] Using a mouse model of dextran sulfate sodium (DSS)-induced colitis, we showed that Ccdc88b-deficent mice are protected against intestinal colitis; likewise, in a T cell transfer model of colitis, Ccdc88b-deficent T cells did not induce colitis in immunocompromised Rag1 −/− mutant mice. 13 Parallel studies in humans showed that the CCDC88B protein and mRNA are elevated in the colon of IBD patients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 In humans, the CCDC88B gene maps within a locus on Chromosome 11 (11q13) that contains >20 genes in linkage disequilibrium that is associated with susceptibility to several inflammatory conditions including psoriasis, primary biliary cirrhosis, MS, and inflammatory bowel disease (IBD). [11][12][13] Using a mouse model of dextran sulfate sodium (DSS)-induced colitis, we showed that Ccdc88b-deficent mice are protected against intestinal colitis; likewise, in a T cell transfer model of colitis, Ccdc88b-deficent T cells did not induce colitis in immunocompromised Rag1 −/− mutant mice. 13 Parallel studies in humans showed that the CCDC88B protein and mRNA are elevated in the colon of IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Using a mouse model of dextran sulfate sodium (DSS)-induced colitis, we showed that Ccdc88b-deficent mice are protected against intestinal colitis; likewise, in a T cell transfer model of colitis, Ccdc88b-deficent T cells did not induce colitis in immunocompromised Rag1 −/− mutant mice. 13 Parallel studies in humans showed that the CCDC88B protein and mRNA are elevated in the colon of IBD patients. Furthermore, expression of CCDC88B mRNA was found to be regulated by cis-acting variants in CD14 + myeloid cells, with CCDC88B mRNA expression correlated positively with disease risk in a cohort of Crohn's disease (CD) patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting gene identified by GWAS was CCDC88B (coiled-coil domain-containing protein 88B) located on chromosome 11q13, which encodes a positive regulator of T-cell maturation and inflammatory function involved in inflammatory bowel diseases [65,66]. Together with other 11q13.1 loci, the rs479777 SNP of CCDC88B was significantly associated with sarcoidosis in a German study.…”
Section: Other Pathways Identified By Gwas In Sarcoidosis Etiologymentioning
confidence: 99%